2021
DOI: 10.18632/aging.203244
|View full text |Cite
|
Sign up to set email alerts
|

IGF IIRα-triggered pathological manifestations in the heart aggravate renal inflammation in STZ-induced type-I diabetes rats

Abstract: Pathological manifestations in either heart or kidney impact the function of the other and form the basis for the development of cardiorenal syndrome. However, the mechanism or factors involved in such scenario are not completely elucidated. In our study, to find the correlation between late fetal gene expression in diabetic hearts and their influence on diabetic nephropathy, we created a rat model with cardiac specific overexpression of IGF-IIRα, which is an alternative splicing variant of IGFIIR, expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Both in vitro and in vivo models have shown that MAPK signaling hypertrophy and mitochondrial‐dependent apoptosis are activated; however, the PI3K‐AKT survival cascade is attenuated when IGF‐IIRα is specifically expressed in cardiomyocytes and cardiac tissues 43 . IGF‐IIRα overexpression in the heart not only causes pathological heart, but also leads to hypertrophic kidney, 44 liver, and testis (unpublished data) in the transgenic rats. In the diabetic transgenic rats, collagen accumulation, renal tubular damage, and renal fibrosis are present in the pathological kidney by enhancement of STAT3 associated mechanism 44 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Both in vitro and in vivo models have shown that MAPK signaling hypertrophy and mitochondrial‐dependent apoptosis are activated; however, the PI3K‐AKT survival cascade is attenuated when IGF‐IIRα is specifically expressed in cardiomyocytes and cardiac tissues 43 . IGF‐IIRα overexpression in the heart not only causes pathological heart, but also leads to hypertrophic kidney, 44 liver, and testis (unpublished data) in the transgenic rats. In the diabetic transgenic rats, collagen accumulation, renal tubular damage, and renal fibrosis are present in the pathological kidney by enhancement of STAT3 associated mechanism 44 .…”
Section: Discussionmentioning
confidence: 92%
“…In the heart, chronic high‐blood glucose levels increase Toll‐like receptor 4 activation and induce downstream pathways, including the NF‐κB inflammatory pathway 22,46 . Additionally, cardiac specific overexpression of IGF‐IIRα elevates the diabetes related inflammation 44 . Hence, IGF‐IIRα may be an inflammation inducer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations